QUaD: A High-Resolution Cosmic Microwave Background Polarimeter - Hinderks, J.R.; Ade, P.; Bock, J.; Bowden, M.; Brown, M. L.; Cahill, G.; Carlstrom, J. E.; Castro, P. G.; Church, S.; Culverhouse, T.; Friedman, R.; Ganga, K.; et al. (The Astrophysical Journal, 2009)
23 pages, 36 figures We describe the QUaD experiment, a millimeter-wavelength polarimeter designed to observe the cosmic microwave background (CMB) from a site at the South Pole. The experiment comprises a 2.64 m Cassegrain telescope equipped with a cryogenically cooled receiver containing an array of 62 polarization-sensitive bolometers. The focal plane contains pixels at two different frequency bands, 100 GHz and 150 GHz, with angular resolutions of 5' and 3farcm5, respectively. The high angular resolution allows observation of CMB temperature and polarization anisotropies over a wide range of scales. The instrument commenced operation in early 2005 and collected science data during three successive Austral winter seasons of observation.